2017
DOI: 10.20471/acc.2017.56.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Head Multislice Computed Tomography Scan in Emergency Department

Abstract: SUMMARY -Th e aim of the study was to examine the prevalence of head injuries, acute stroke and brain tumors obtained from computed tomography (CT) scans in the emergency department (ED) during a one-year period. We also assessed the potential eff ect of seasons on the occurrence of stroke, head trauma and tumors found on CT scans, expressed in monthly intervals. Th is retrospective review included all patients that underwent emergency head CT from the hospital database. A total of 3888 head CT examinations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…Demographic data and symptoms of brain abscess present on admission to the hospital did not differ from other studies ( 4 , 7 , 9 , 20 - 26 ). The current study showed male predominance, which is consistent with current literature, since men are more prone to predisposing factors for brain abscess ( 4 , 7 , 9 , 20 - 27 ). However, the study did not find any correlation between gender and outcome.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Demographic data and symptoms of brain abscess present on admission to the hospital did not differ from other studies ( 4 , 7 , 9 , 20 - 26 ). The current study showed male predominance, which is consistent with current literature, since men are more prone to predisposing factors for brain abscess ( 4 , 7 , 9 , 20 - 27 ). However, the study did not find any correlation between gender and outcome.…”
Section: Discussionsupporting
confidence: 93%
“…When comparing outcomes in patients treated with standard craniotomy and stereotactic aspiration, several studies report on better outcome in patients treated with stereotactic aspiration and some report that there are no differences in the outcome regarding surgical strategies ( 1 , 3 - 5 , 7 - 9 , 12 , 14 - 18 , 21 , 25 - 27 ). Important characteristics that might influence the outcome and studies reporting such impact are presented in Table 7 .…”
Section: Discussionmentioning
confidence: 99%